Humoral immune factor changes in group of patients with Non-muscle invasive bladder cancer treated with intravesical therapy. - Aldabagh, Muhammed A. H.; Hassan, Jabbar S.; Abdelkareem, Montaha; Atala, Mohmmed L. (Journal of the Faculty of Medicine Baghdad, 2018)
Background: Bladder cancer (BC) one of the most common urologic cancer characterized by the highest recurrence rate, many types belong to BC, but most common of them worldwide are transitional cell carcinoma(TCC) which constitute about 90-95% cases, squamous cell carcinoma (SCC) and adenocarcinomasObjective: This study was designed to evaluate parameters of humoral immunity in Non-muscle invasive (superficial or early) bladder cancer patients in Iraq that may provide a new insight into the future of immunotherapies development and BC management.Materials and methods: Fifty-nine volunteer's patients ranged from 24 to 83years old, and 30 control individuals ranged from 51-80 years old, who attended and admitted to Hospital of Gazi AL-Harery in medical city of Baghdad, and Al-Emamain Al-Khadhemain Teaching hospital was recruited in this investigation. The sera of study groups were subjected to serological test to estimate the levels of (IgA, IgG, IgM and C3) by Single radial immunodiffusion (sRID) assay and Enzyme-Linked immunosorbent assay (ELISA) was used to estimate the serum levels of IL-10.Results: The ages ranged from 24 to 83years (females: 26 to 72years, males: 38 to 83years) with male to female ratio 4.9:1 and ages of controls ranged from 51 to 80years (females: 54 to 70years, males: 51 to 80years) with male to female ratio 2.75:1, the mean ages of cases and controls groups were (61.65±11.04) , current study showed significance dropping in C3 levels in patients control and Mitomycin C groups compared with apparently healthy, levels of IgM showed significant elevation in BCG group compared with apparently healthy group while patients control and mitomycin C groups showed insignificant elevation of IgM. Levels of IgG showed significant elevation in patients control and mitomycin C groups compared with apparently healthy group while in BCG group showed no differences. Serum levels of IL-10 showed no differences between apparently healthy group and each of patient's groups, also showed no differences within patient's groupsConclusions: Bladder cancer is a common urologic malignancy in male than female patients enrolled in this study. Intravesical BCG or Mitomycin C leading to effective anti-bladder cancer immunity in the majority of Patientsالخلفية: سرطان المثانة   واحدة من أكثر سرطان المسالك البولية شيوعا تتميز أعلى معدل تكرار، العديد من الأنواع تنتمي إلى  سرطان المثانة ، ولكن الأكثر شيوعا منهم في جميع أنحاء العالم هي سرطان الخلايا الانتقالية   التي تشكل حوالي 90-95٪  من الحالات.  الهدف: تم تصميم هذه الدراسة لتقييم المعلمات من المناعة الخلطية   في  مرضى سرطان المثانة في العراق التي قد توفر نظرة جديدة في مستقبل    العلاج المناعي لهذا المرض . المواد والأساليب: تراوح عدد المرضى المتطوعين الذين تتراوح أعمارهم بين 24 و 83 سنة، و 30 فردا من الأشخاص الذين تتراوح أعمارهم بين 51 و 80 عاما، والذين حضروا إلى مستشفى غازي الحريري في مدينة بغداد الطبية، و مدينة الامامين الكاظمين   . تم اختبار مصل الدم من مجموعات الدراسة لاختبار المصلية لتقدير مستويات(IgA, IgG, IgM and C3 ) من خلال فحص المناعي الشعاعي واحد   وبواسطة  فحص (إليسا)     النتائج: تراوحت الأعمار من 24 إلى 83 سنة (الإناث: 26 إلى 72 سنة، ذكور: 38 إلى 83 سنة) مع نسبة الذكور إلى الإناث 4.9: 1 وأعمار الضوابط تراوحت بين 51 إلى 80 سنة (الإناث: 54 إلى 70 سنة، ذكور: 51 إلى (61.65 ± 11.04)، وأظهرت الدراسة الحالية انخفاض معنوي في مستويات C3 في السيطرة على المرضى ومجموعات ميتوميسين C مقارنة بمستويات سليمة على ما يبدو من  IgM أظهرت ارتفاع كبير في مجموعة  IgGمقارنة مع مجموعة   صحية بينما أظهرت الدراسة  السيطرة على المرضى والمجموعات ميتوميسين C ارتفاع كبير من IgM. وأظهرت مستويات  IgG ارتفاع ملحوظ في السيطرة على المرضى والمجموعات ميتوميسين C مقارنة مع مجموعة على ما يبدو صحي   أظهرت مستويات مصل الدم من  IL10 عدم وجود فروق بين المجموعة الصحية على ما يبدو وكل من مجموعات المريض، كما أظهرت أي اختلافات داخل مجموعات المريضالاستنتاجات: سرطان المثانة هو الأورام الخبيثة المسالك البولية شيوعا في الذكور من الإناث المرضى المسجلين في هذه الدراسة.  BCG أو ميتوميسين C   يؤدي إلى فعالية المناعة المضادة لسرطان المثانة في غالبية المرضى